2016
DOI: 10.1016/j.eurpolymj.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

New habits in branched polyethylene single crystals

Abstract: Faceted polymer single crystals obtained from solution have been examined for decades. Most of the studies have been performed with linear polyethylene. It is well known that solution-grown linear polyethylene single crystals may exhibit different and often complex morphologies and habits. However, the effect of molecular architecture (i.e., short chain branching) in the morphology of the single crystals remains practically unexplored. At the highest crystallization temperature investigated, the shape of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
2
1
0
Order By: Relevance
“…In these studies, interesting phenomena were observed including a decrease in the trans/gauche ratio and crystal sizes with SCB, branch inclusion in the crystals for systems containing the shorter branches, exclusion of longer branches from the crystals and inhibition of crystallization for systems with more than 50 SCB per 1,000 C atoms. All these phenomena are in fairly good agreement with experimental observations in single crystals of SCB PE [244,259]. However, a more realistic description of the systems that explicitly takes into account solvent molecules is not an easy computational task.…”
Section: Crystallization Of Single Chainssupporting
confidence: 86%
See 2 more Smart Citations
“…In these studies, interesting phenomena were observed including a decrease in the trans/gauche ratio and crystal sizes with SCB, branch inclusion in the crystals for systems containing the shorter branches, exclusion of longer branches from the crystals and inhibition of crystallization for systems with more than 50 SCB per 1,000 C atoms. All these phenomena are in fairly good agreement with experimental observations in single crystals of SCB PE [244,259]. However, a more realistic description of the systems that explicitly takes into account solvent molecules is not an easy computational task.…”
Section: Crystallization Of Single Chainssupporting
confidence: 86%
“…It should be noted here that quite similar results for the temperature dependences of linear PE lattice parameters can be obtained using quasi-harmonic lattice dynamics coupled to molecular mechanics FFs [256,257]. [121][122][123], () EH copolymers, Otegui et al [243] and EH single-crystals, Vega et al [244,259]. Closed symbols represent computer simulations of lattice parameters including branching [255] Less studied through computer simulations have been the impacts of SCB on orthorhombic lattice parameters.…”
Section: The Orthorhombic Unit Cellsupporting
confidence: 68%
See 1 more Smart Citation